Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, Pemahaman Teknologi Informasi dan Sosialisasi Terhadap Penerapan SAK EMKM : Studi Kasus UMKM di Kecamatan Rungkut Kota Surabaya - Arlangga Cahyo Gumelar Herdianto; R. Sjarief Hidajat (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to examine the effect of education level, accounting understanding, information technology understanding and socialization on the implementation of SAK EMKM. The data of this study are primary data. The questionnaire was given to MSME actors in Rungkut District, Surabaya City. The sample was taken using the probability sampling method, namely random sampling, and 100 MSMEs registered in Rungkut District were obtained. This study uses SEM-PLS Analysis using the SmartPLS 4.0 application. The results indicate information technology understanding and socialization influencing the implementation of SAK EMKM. While the level of education and accounting understanding did not have a positive influence on it. This study has several shortcomings and limitations. Therefore, the next study can further develop the discussion and more accurate results by providing other variables that represent the factors of SAK EMKM implementation.